1980
DOI: 10.1177/00034894800890s313
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surgical Alterations of the Tensor Veli Palatini Muscle onc Eustachian Tube Function

Abstract: Previous studies in humans have indicated that functional obstruction of the eustachian tube (ET) is an important factor in the pathogenesis of otitis media with effusion (OME). This type of obstruction appears to be related to the structural properties of the tube, or to an inefficient active tubal opening mechanism, or both. In this study, functional ET obstruction was created in 22 rhesus monkeys ( Macaca mulatta) by surgically altering the tensor veli palatini (TVP) muscle using three different procedures:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0
3

Year Published

1982
1982
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 17 publications
0
32
0
3
Order By: Relevance
“…23 The relationship between the tensor veli palatine muscle and middle ear aeration and tubal function was shown by several types of surgical alteration of this muscle. 32 In a clinical study, Neel et al 33 have shown that middle ear volume increased progressively and hearing was restored to normal levels by additional ventilation of the middle ear in patients with middle ear effusion.…”
Section: Discussionmentioning
confidence: 99%
“…23 The relationship between the tensor veli palatine muscle and middle ear aeration and tubal function was shown by several types of surgical alteration of this muscle. 32 In a clinical study, Neel et al 33 have shown that middle ear volume increased progressively and hearing was restored to normal levels by additional ventilation of the middle ear in patients with middle ear effusion.…”
Section: Discussionmentioning
confidence: 99%
“…The predictive accuracy of this model is demonstrated by the close similarity between the simulated MEEPG trajectory at an ET opening efficiency of 0 and the observed trajectory for monkeys with experimentally abolished ET openings (Cantekin et al, 1980; Casselbrant et al, 1988). Also, it is known that ET opening efficiency has both a constitutive and a situational component and that constitutive efficiency is downgraded temporarily during conditional situations such as an extant viral upper respiratory infection (Doyle et al, 2014).…”
Section: 0 Discussionmentioning
confidence: 82%
“…The significance of a well-functioning tensor veli palatini muscle is underlined in three studies in which a functional Eustachian tube obstruction model was created by affecting the muscle through surgical manipulation or injection of paralyzing agents [2527]. Cantekin et al [25] performed various surgical alterations of the tensor veli palatini muscle in rhesus monkeys: (1) complete excision of the muscle, (2) transection of the superficial muscle bundle, and (3) transposition, realized by isolating the tendinous portion of the tensor veli palatini muscle and lifting it over the hamulus, giving it a more medial position.…”
Section: Discussionmentioning
confidence: 99%
“…Cantekin et al [25] performed various surgical alterations of the tensor veli palatini muscle in rhesus monkeys: (1) complete excision of the muscle, (2) transection of the superficial muscle bundle, and (3) transposition, realized by isolating the tendinous portion of the tensor veli palatini muscle and lifting it over the hamulus, giving it a more medial position. In the large majority of the ears in the excision group, middle ear effusion developed within 5 weeks and in most cases became a chronic condition.…”
Section: Discussionmentioning
confidence: 99%